MEMBANGUN KECERDASAN EMOSIONAL SISWA MELALUI PENDEKATAN PEMBELAJARAN KOOPERATIF - Firdausiyah, Nadiatul; Manshur, Umar (LP2M IAIN Sultan Amai Gorontalo, 2025)
This study aims to explore the effectiveness of a cooperative learning approach in developing students' emotional intelligence. Emotional intelligence is an individual's ability to recognize, understand, and manage their own emotions and establish healthy social relationships, which are crucial for supporting successful learning and character development. A cooperative learning approach provides space for students to interact, collaborate, and respect each other in the learning process, thus contributing to the strengthening of aspects of emotional intelligence such as empathy, self-control, social awareness, and communication skills. This study used a descriptive qualitative method with a case study type, with data obtained through observation, interviews, and documentation techniques in one Islamic junior high school (MTs). The results showed that the consistent implementation of cooperative learning was able to create a learning environment conducive to the development of students' emotional intelligence. Strategies such as dividing students into heterogeneous groups, assigning shared responsibilities, and group reflection proved effective in fostering mutual respect, open communication, and increasing self-awareness. These findings indicate that cooperative learning not only encourages academic achievement but also plays an important role in developing students' character and emotional intelligence.